Some properties of certain analytic functions - Owa, Shigeyoshi; Yavuz Duman, Emel (My University, 2012)
Applying the subordinations for analytic functions f(z) normalized by f(0) = 0 and f 0 (0) = 1 in the open unit disk U, some properties of f(z) are discussed.
Keywords: Analytic; subordination; starlike; convex